Toward autonomous measurements of photosynthetic electron transport rates: An evaluation of active fluorescence‐based measurements of photochemistry. (18th March 2015) - Silsbe, Greg M.; Oxborough, Kevin; Suggett, David J.; Forster, Rodney M.; Ihnken, Sven; Komárek, Ondřej; Lawrenz, Evelyn; Prášil, Ondřej; Röttgers, Rüdiger; Šicner, Michal; Simis, Stefan G.H.; Van Dijk, Mark A.; et al.
Abstract: This study presents a methods evaluation and intercalibration of active fluorescence‐based measurements of the quantum yield ( ϕ PSII ′ ) and absorption coefficient ( a PSII ) of photosystem II (PSII) photochemistry. Measurements of ϕ PSII ′, a PSII, and irradiance ( E ) can be scaled to derive photosynthetic electron transport rates ( P e ), the process that fuels phytoplankton carbon fixation and growth. Bio‐optical estimates of ϕ PSII ′ and a PSII were evaluated using 10 phytoplankton cultures across different pigment groups with varying bio‐optical absorption characteristics on six different fast‐repetition rate fluorometers that span two different manufacturers and four different models. Culture measurements of ϕ PSII ′ and the effective absorption cross section of PSII photochemistry ( σ PSII, a constituent of a PSII ) showed a high degree of correspondence across instruments, although some instrument‐specific biases are identified. A range of approaches have been used in the literature to estimate a PSII ( λ ) and are evaluated here. With the exception of ex situ a PSII ( λ ) estimates from paired σ PSII and PSII reaction center concentration ( [ RCII ] ) measurements, the accuracy and precision of in situ a PSII ( λ ) methodologies are largely determined by the variance of method‐specific coefficients. The accuracy and precision of these coefficients are evaluated, compared to literature data, and discussed within a framework of autonomous P e measurements. This study supports the application of an instrument‐specific calibration coefficient ( K R ) that scales minimum fluorescence in the dark ( F 0 ) to a PSII as both the most accurate in situ measurement of a PSII, and the methodology best suited for highly resolved autonomous P e measurements.© 2014 Association for the Sciences of Limnology and Oceanography